"Lowe syndrome: A particularly severe phenotype without clinical kidney involvement". Issue 2 (11th December 2017) - Abdalla, Ebtesam; El‐Beheiry, Ahmed; Dieterich, Klaus; Thevenon, Julien; Fauré, Julien; Rendu, John
Abstract : Lowe syndrome (LS) is a very rare disorder of phosphatidylinositol metabolism, which manifests with a complex phenotype comprising a clinical triad encompassing major abnormalities of the eyes, the kidneys, and the central nervous system. We are reporting a 23‐year‐old Egyptian male with a severe phenotype of LS with a minimal kidney disease. Direct sequencing of the OCRL gene detected a p.His375Arg mutation in the catalytic domain of the protein. The patient suffered from bilateral congenital cataracts and glaucoma, striking growth deficiency, severe psychomotor disability, a severe osteopathy, and seizures, but only minimal renal dysfunction. Although the biological mechanisms underlying the pathophysiology of LS manifestations is yet unclear, it has been proposed that growth delay and osteopathy are linked to a renal dysfunction. This report, however, argues this association and suggests that kidney dysfunction may partially explain the growth deficiency and bone abnormalities, but other still undefined factors might have a potential impact.